Developing a local academic English listening test using authentic unscripted audio-visual texts. (July 2022) - Park, Yena; Lee, Senyung; Shin, Sun-Young
Despite consistent calls for authentic stimuli in listening tests for better construct representation, unscripted texts have been rarely adopted in high-stakes listening tests due to perceived inefficiency. This study details how a local academic listening test was developed using authentic unscripted audio-visual texts from the local target language use (TLU) domain without compromising the reliability of the test results and validity of the score interpretations. The purpose of the listening test was to identify international students who need additional language support at a U.S. university. We show that efficiency persists when using authentic unscripted texts that are representative of the local context both at the test development phase and at the classification phase where placement decisions are made in a dependable manner. Expert judgments highlighted the improved correspondence of the listening test using locally sourced audio-visual texts to the local TLU domain, providing additional support for using the listening test for local placement purposes. Additionally, dimensionality assessments demonstrated that test design decisions inevitably entailed with using authentic unscripted texts did not threaten the internal structure of the test. We argue that local resources are indispensable in developing authentic test stimuli and in supporting the validity of local test interpretation and use.